1999
DOI: 10.1034/j.1399-0039.1999.530101.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of trophoblast HLA‐G: polymorphism, isoforms, imprinting and expression in preimplantation embryo

Abstract: There is considerable interest in human HLA-G arising from the observation that it is expressed selectively on the surface of extravillous trophoblast, the fetal cell population directly in contact with the mother. We investigated several aspects of the molecular biology of this unusual molecule. Limited polymorphism at the nucleotide level, and even more restricted variation at the amino acid level, was found in our Caucasian population. A further unusual aspect of HLA-G is the occurrence of alternatively spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 54 publications
6
123
0
3
Order By: Relevance
“…Surprisingly, no data on the proportions of embryos expressing HLA-G in each group was given, so comparison with our study is not possible. In another report, Hiby et al (16) found no HLA-G mRNA in 11 preimplantation embryos ranging from the 2 cell to the blastocyst stage using nested primers for full-length HLA-G. Their methodology differed from ours in that they isolated RNA from zona intact embryos rather than removing the zona first and used standard phenol-chloroform extraction instead of the magnetic bead method, both of which may affect the yields of RNA. The primers used in both the studies of Jurisicova and Hiby would have amplified all the different isoforms, giving the total HLA-G mRNA expression, but the hemi-nested RT-PCR system used by Jurisicova et al (4,5) was probably less sensitive than our specific nested RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no data on the proportions of embryos expressing HLA-G in each group was given, so comparison with our study is not possible. In another report, Hiby et al (16) found no HLA-G mRNA in 11 preimplantation embryos ranging from the 2 cell to the blastocyst stage using nested primers for full-length HLA-G. Their methodology differed from ours in that they isolated RNA from zona intact embryos rather than removing the zona first and used standard phenol-chloroform extraction instead of the magnetic bead method, both of which may affect the yields of RNA. The primers used in both the studies of Jurisicova and Hiby would have amplified all the different isoforms, giving the total HLA-G mRNA expression, but the hemi-nested RT-PCR system used by Jurisicova et al (4,5) was probably less sensitive than our specific nested RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Duplex PCR was carried out for 40 amplification rounds in the presence of TaqMan Universal PCR Master Mix, using the predeveloped TaqMan assay reagent GAPDH as an endogenous control [probe with VIC reporter and 6-carboxytetramethylrhodamine (TAMRA) quencher (Applied Biosystems)], HLA-G-specific probe located in exon 5 [200 nM; Applied Biosystems: 5Ј-CACTGGAGCTG-CGGTCGCTGCT; 6-carboxyfluorescein (FAM) reporter and TAMRA quencher] and HLA-G-specific primers [300 nM (Qbiogene, Illkirch, France): forward 5Ј-CTGGTTGTCCTTG-CAGCTGTAG; reverse 5Ј-CCTTTTCAATCTGAGCTCT-TCTTTCT] we designed, using PRIMER EXPRESS software. The primers were selected to amplify all alternative forms of HLA-G transcripts, including those deleted in the 3ЈUTR because of the presence of a 14-bp polymorphism (57). The specificity of HLA-G cDNA amplifications was assessed on various cell lines that did not express classical and nonclassical HLA class I genes and that did or did not express HLA-class II genes (not shown).…”
Section: Methodsmentioning
confidence: 99%
“…19 In addition, a 14 bp insertion/deletion polymorphism has been reported in the 3 0 -untranslated region (UTR) of exon 8. 20 HLA-G alleles exhibiting the 14 bp insertion ( þ 14 bp) undergo an alternative splicing that removes 92 bases from 3 0 UTR, 21 influencing the stability of HLA-G mRNA. 22 Although removal of the 92 bases produces a more stable mRNA, the presence of þ 14 bp has been associated with a lower mRNA production.…”
Section: -15mentioning
confidence: 99%